Population, Migration, and Socioeconomic Outcomes among Island and Mainland Puerto Ricans : La Crisis Boricua - Mora, Marie T., 1969-; Dávila, Alberto E.; Rodríguez, Havidán (Lexington Books, 2018)
At the landmark centennial anniversary of the 1917 Jones-Shafroth Act, which granted Puerto Ricans U.S. citizenship, the island confronts an unfolding humanitarian crisis initially triggered by an acute economic crisis surging since 2006. Analyzing large datasets such as the American Community Survey and the Puerto Rican Community Survey, this book represents the first comprehensive analysis of the socioeconomic and demographic consequences of "La Crisis Boricua" for Puerto Ricans on the island and mainland, including massive net outmigration from the island on a scale not seen for sixty years; a shrinking and rapidly aging population; a shut-down of high-tech industries; a significant loss in public and private sector jobs; a deteriorating infrastructure; higher sales taxes than any of the states; $74 billion in public debt plus another $49 billion in unfunded pension obligations; and defaults on payments to bondholders. This book also discusses how the socioeconomic and demographic outcomes differ among stateside Puerto Ricans, including recent migrants, in traditional settlement areas such as New York versus those in newer settlement areas such as Florida and Texas. Florida is now home to 1.1 million Puerto Ricans (essentially the same number as those living in New York) and received a full third of the migrants from the island to mainland during this time. Scholars interested in the transition of migrants into their receiving communities (regardless of the Puerto Rican case) will also find this book to be of interest, particularly with respect to the comparative analyses on earnings, the likelihood of being impoverished, and self-employment.